KARAKTERISTIK FISIKOKIMIA DAGING SAPI BALI (Longissimus dorsi) HASIL MATURASI: IMPLIKASI PEMBERIAN ASAP CAIR DALAM PAKAN - Syamsuddin Syam; La Ode Rahman Musawa; Syahriana Sabil (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2026)
Bali cattle beef is a superior local commodity and an excellent source of animal protein for humans. Improving meat quality can be achieved through innovative supplemental feeding, specifically with the addition of liquid smoke. The material used in this study was beef from the Longissimus dorsi muscle of Balinese cattle. These cattle were given supplemental feed containing liquid smoke at varying levels (0%, 1%, and 2%), combined with four different aging (maturation) periods: 0, 2, 4, and 6 days. The observed parameters included the degree of acidity (pH), shear force, and fat oxidation levels (TBA). The study employed a completely randomized design (CRD) with a 3 x 4 factorial arrangement and three replications. The results indicated that the addition of liquid smoke to the feed and the aging period had a significant effect on pH stability and the inhibition of fat oxidation (TBA) in Balinese beef. Furthermore, increasing the liquid smoke level and prolonging the aging period decreased the pH value, while increasing the shear force value and fat oxidation levels in the Longissimus dorsi muscle of fattened Balinese cattle.